An Improved Diffuse-Interface Lattice Boltzmann Method for Particulate Flows (Communications in Computational Physics, 2024)
In this paper, an improved diffuse-interface lattice Boltzmann method forparticulate flows is developed. In this method, the difference in viscosity betweenthe fluid and the particle is considered, and a smooth function is introduced to thecollision term of the evolution equation. Some simulations are performed to test themethod, and the numerical results show that, compared to the previous diffusion-interface lattice Boltzmann method [J. Liu et al., Comput. Fluids 233 (2022) 105240]which only has a first-order accuracy in space, the present one has a second-orderconvergence rate in space.